THEORETICAL ANALYSIS OF MEASURED METOCEAN DATA IN TIME AND FREQUENCY DOMAINS FOR MALAYSIAN WATERS - DUONG, VANNAK (2017)
The offshore structures are particularly at risk with any extreme motions initiated by metocean data such as wind speed and wave height. These metocean loads form the critical and prerequisite criteria in the design and operation of offshore structure. In Malaysian waters, most of the design and operation of offshore structure is based on the extreme value in other area. Consequently, the study of the measured metocean data on statistical properties and power spectral densities in Malaysian water is conducted based on the data obtained in Malaysian waters from 1999 to 2008. The missing data was found during measurement at fields, these missing data was replaced by the linear interpolation method for reliability in the analysis.